Comparison between Early and Late Drain Released after Modified Radical Mastectomy Surgery through Observation over Proportion of Percutaneous Aspiration Technique of Seroma Production in Surgical Polyclinic of Dr. Soetomo Hospital, Surabaya - Parlindungan, Putra Gelar; Ishardyanto, Hantoro (Folia Medica Indonesiana, 2020)
Surgery is the most frequent indication and major therapy in the management of malignancy of breasts. Drain is one method to drainage the seroma formed after the modified radical mastectomy surgery. The drain-release protocol varies in each hospitals. This study aimed to compare the proportion of percutaneous aspiration in patients with early drain release with late drain release in postoperative MRM patients. The present study is a prospective cohort study comparing the proportion of percutaneous aspiration in 30 patients with early drain released with 30 patients with late drain release in Dr. Soetomo hospital The recording of the proportion of aspiration actions was conducted serially on days 3, 7, 10, and 14 after drain release. Recording of age, nutritional status (BMI), tumor histopathology type, stage, shoulder mobilization time, obliterant usage, wound infections surgery, flap necrosis and hematom were analyzed to find out if there was any effect on seroma event In our study we did not find the difference in serum aspiration proportions both in the early and late drain observation group. Age factor, nutritional status (BMI), histopathology type, stage, shoulder mobilization time, obliterant use, presence of surgical wound infection, flap necrosis and hematom did not differ significantly statistically to seroma events. Statistically, there was no difference in the proportion of percutaneous aspiration in a group of observed patients with early and late drain release. Late drain release can be avoided to potentially harm the patient in decreasing the lives' quality of the patients.